2020
DOI: 10.1080/09638288.2020.1720318
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of fatigue in daily life of people with acquired brain injury: a qualitative study

Abstract: To develop an in-depth understanding of how survivors of acquired brain injury (ABI) experience fatigue and how fatigue affects everyday life. Materials and methodsWe conducted semi-structured in-depth interviews with 16 adults with ABI fatigue, recruited from support groups in south east UK. Interviews were analysed using the frameworks method. ResultsWe developed four themes: experiencing fatigue in the context of everyday activities, struggling to make sense of fatigue, coping with fatigue, adjusting social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
1
15
0
1
Order By: Relevance
“…The findings indicate that rehabilitation efforts aimed at helping patients re-establish a coherent sense of self and their future, and to reconnect with social resources, might lessen their risk of fatigue in the early stages of rehabilitation. This latter point was supported in a recent qualitative study [ 81 ], in which the use of social support was identified as a promising treatment angle for breaking vicious cycles for perpetuation and exacerbation of fatigue after brain injury.…”
Section: Discussionmentioning
confidence: 69%
“…The findings indicate that rehabilitation efforts aimed at helping patients re-establish a coherent sense of self and their future, and to reconnect with social resources, might lessen their risk of fatigue in the early stages of rehabilitation. This latter point was supported in a recent qualitative study [ 81 ], in which the use of social support was identified as a promising treatment angle for breaking vicious cycles for perpetuation and exacerbation of fatigue after brain injury.…”
Section: Discussionmentioning
confidence: 69%
“…Distinguishing between different types of fatigue (e.g. physical and mental fatigue) and how these are exacerbated by activities and environments is necessary when advising on self-management strategies ( 41 ). Currently, there is limited consensus regarding the definition of poststroke fatigue or its underlying mechanisms, which underscores the importance of further research.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired brain injury (ABI) is an injury to the brain that is not hereditary, degenerative, congenital, or brought about by birth trauma; it happens after birth 1 . ABI includes both brain injuries with a non-traumatic cause (such as brain tumours and stroke) and with a traumatic cause (such as automobile crashes and falls) 2 . In Ireland, there does not currently exist an adequate system for registering the prevalence and incidence and of ABI on an international and national basis, but informal estimates from the Irish National Audit of Stroke Care and data from the Hospital In-Patient Enquiry scheme indicates that each year in the country around 20,000 brain injuries occur 3 .…”
Section: Introductionmentioning
confidence: 99%